Оператори iнтерлiнацiї лагранжевого типу на системi взаємно перпендикулярних прямих з використанням узагальнених полiномiв - Литвин, О.М.; Штепа, Н.I. (Видавничий дім "Академперіодика" НАН України, 2008)
Interlineation operators of the functions of two variables (blending function interpolation) with traces of a given function on a system of mutually perpendicular straight lines is investigated. For the construction of these operators, we use generalized polynomials which are not algebraic polynomials. Some examples are considered.